The role of Th cell subsets in the control of Helicobacter infections and in T cell-driven gastric immunopathology - Müller, Anne; Hitzler, Iris; Kohler, Esther; Engler, Daniela B.; Sayi Yazgan, Ayca (Frontiers in Immunology, 2012)
Chronic infection with the gastric bacterial pathogen Helicobacter pylori causes gastric adenocarcinoma in a particularly susceptible fraction of the infected population. The intestinal type of gastric cancer is preceded by a series of preneoplastic lesions that are of immunopathological origin, and that can be recapitulated by experimental infection of C57BL/6 mice with Helicobacter species. Several lines of evidence suggest that specific T cell subsets and/or their signature cytokines contribute to the control of Helicobacter infections on the one hand, and to the associated gastric preneoplastic pathology on the other. Here, we have used virulent H. pylori and H. felis isolates to infect mice that lack α/β T cells due to a targeted deletion of the T cell receptor β-chain, or are deficient for the unique p35 and p19 subunits of the Th1- and Th17-polarizing cytokines interleukin (IL)-12 and IL-23, respectively. We found that α/β T cells are absolutely required for Helicobacter control and for the induction of gastric preneoplastic pathology. In contrast, neither IL-12-dependent Th1 nor IL-23-dependent Th17 cells were essential for controlling the infection; IL-12p35-/- and IL-23p19-/- mice did not differ significantly from wild type animals with respect to Helicobacter colonization densities. Gastritis and gastric preneoplastic pathology developed to a similar extent in all three strains upon H. felis infection; in the H. pylori infection model, IL-23p19-/- mice exhibited significantly less gastritis and precancerous pathology. In summary, the results indicate that neither Th1 nor Th17 cells are by themselves essential for Helicobacter control; the associated gastric pathology is reduced only in the absence of Th17-polarizing IL-23, and only in the H. pylori, but not the H. felis infection model. The results thus suggest the involvement of other, as yet unknown T cell subsets in both processes.